Histiricographical Analyz of the Problem of Law Education of Junior Teenagers of General Educational Establishments - Olena Polishchuk (Pedagogical Discourse, 2013)
The author of the article studies theoretical bases of law education of pupils. Integral conception of the importance, complicacy of this problem through the integration of scientific works on philosophy, pedagogics, psychology, sociology has been given. On the basis of the analysis of scientific-pedagogical sources the essence of law education of young people at the modern stage has been revealed. Different approaches to the interpretation of the notion «law education» have been cleared up. The specificity of the law education of the pupils, its content, conceptions, aim, goals, tasks, methodological bases in the world and domestic pedagogical thought have been analyzed. The attention is accentuated at the interconnection of the law education with the law culture and the law consciousness of a personality.